Percutaneous Full Endoscopic Management of Lumbar Posterior Edge Separation in Adolescents - Peng, Chen; Zhou, Chuanli; Zhu, Kai; Zhang, Hao; Tu, Qihao; Ma, Xuexiao; Liu, Lei (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Purpose Lumbar posterior edge separation is a common disorder with lumbar disc herniation (LDH) in adolescents. Over the years, there has been a lack of an acknowledged assessment and plan. The purpose of this study was to elucidate the feasibility of all sufferers who have received percutaneous full endoscopic treatment for lumbar posterior edge separation in adolescents.Methods Case series of sufferers with lumbar posterior edge separation who underwent surgery in the Affiliated Hospital Qingdao University between February 2017 and December 2018 were reviewed, including 15 males and 9 females. Preoperative and postoperative visual analogue scale (VAS) scores and the Korean Version of the Oswestry disability index (K-ODI) scores were used to evaluate the clinical outcomes.Results All sufferers were followed up for 6 to 12 months, with an average time of 10.7 months. The postoperative VAS scores of low back pain and leg pain and ODIs were significantly different from the preoperative scores (p < 0.05). According to the modified Mac Nab criteria, the results were excellent in 17 cases and good in 7 cases.Conclusions Percutaneous full endoscopic treatment can effectively achieve neurological functional recovery in sufferers with favorable efficacy and safety.
Keywords: percutaneous full endoscopic; lumbar posterior edge separation; visible foraminoplasty